PENGARUH KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT. PEGADAIAN (PERSERO) KANTOR WILAYAH V MANADO - Monica G. E. Pandelaki; Jeaneta J. Rumerung (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2022)
Human resources are very important organizational assets, namely as thinkers, planners, and controlling organizational activities, therefore their existence in an organization cannot be replaced by other resources. Human resources as the driving force of the organization to communicate every time they carry out their organizational activities. Continuous good communication is needed to produce good performance from employees. The purpose of this study is to determine the effect of communication on employee performance at PT. Pegadaian (PERSERO) Kantor Wilayah V Manado. This type of research is quantitative research and research methods use research methods Descriptive namely describing phenomena or problems that occur in an object of research. The population taken is all the employees in PT. Pegadaian (PERSERO) Kantor Wilayah V Manado with the total of 55 employees while the sample is 30 respondents. The analysis used is regression analysis and simple correlation. The results of the research analysis show that Communication has a very strong and significant relationship to Employee Performance in PT. Pegadaian (PERSERO) Kantor Wilayah V Manado with R=0,718 and coefficient determination 51,6% determine of communication by employee performance and 48,4% is determine with another factor. For that reason, communication needs to be considered by companies in general in improving employee performance, so that what becomes the company's goals can be achieved. And as a suggestion, so that communication goes well, employees should need to maintain good relations with their leaders or fellow employees. In order to create good communication in the company so that work is carried out smoothly and improve employee performance.